Grewia tenax-Mediated Silver Nanoparticles as Efficient Antibacterial and Antifungal Agents - Priyanka Yadav; Monisha Singhal; Sreemoyee Chatterjee; Surendra Nimesh; Nidhi Gupta (Nanomaterials and Nanotechnology)
Nanoparticles have gained immense interest as probable drug molecules against microbial infections. Metal nanoparticles synthesized via exploring the reduction potential and capping activity of plants were found to have remarkable antimicrobial activity. The synthesis was conducted without hazardous chemicals and generation of toxic waste products. The focus of the study was, therefore, to investigate the efficacy of silver nanoparticles biosynthesized using Grewia tenax leaf extract as an antibacterial, antibiofilm, and antifungal therapeutic agent. The silver nanoparticles (GTAgNPs) were synthesized using optimized conditions of 2.5 mM AgNO3 and 1 : 10 ratio of 10% extract at 37°C on continuous stirring. The characterization was done by UV-visible spectroscopy, DLS, SEM, zeta potential, and FTIR. The antibacterial activity of GTAgNPs against both Gram (+) Bacillus cereus and Staphylococcus aureus and Gram (−) Escherichia coli and Pseudomonas aeruginosa bacteria via zone of inhibition, MIC, and MBC was analysed. The inhibitory effect of silver nanoparticles on biofilm formation was also observed against these bacteria. These nanoparticles were then evaluated for their potential antifungal activity against Candida albicans and Aspergillus niger by observing fungal growth inhibition. The probable mechanism of antimicrobial activity by GTAgNPs was studied by scanning electron microscopy which showed the significant formation of pores on the cell surface in GTAgNPs-treated microbial cells, leading to the death of the microbial cell. All these studies concluded that GTAgNPs possess the potent antimicrobial potential and can be employed as antimicrobial therapeutic agents.